2004
DOI: 10.1089/end.2004.18.735
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Durability of Leading Flexible Ureteroscopes

Abstract: All ureteroscopes performed similarly by objective and subjective criteria. The largest and newest instruments were significantly more durable than the smaller ones, even in the hands of numerous endoscopists. This finding has significant implications for the cost-effectiveness of the various ureteroscopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Main causes of flexible ureteroscope repair were represented by loss of deflection, perforation of inner lining by laser fiber, and breakdown of optical fibers. [567] In our series, ODF-URS (URF-V) was broken while approaching a lower calyx stone at an extremely acute infundibulo-pelvic angle. Several technical tricks and accessory instruments were presented during a number of studies aiming to prolong F-URS functionality.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Main causes of flexible ureteroscope repair were represented by loss of deflection, perforation of inner lining by laser fiber, and breakdown of optical fibers. [567] In our series, ODF-URS (URF-V) was broken while approaching a lower calyx stone at an extremely acute infundibulo-pelvic angle. Several technical tricks and accessory instruments were presented during a number of studies aiming to prolong F-URS functionality.…”
Section: Discussionmentioning
confidence: 83%
“…They reported that between 10 and 34 procedures were performed before a malfunction requiring major repair occurred. [6] Considering that ODF-URS (URF-V) was used for 5430 min (90 h and 30 min) during 60 procedures with no need of repair, progresses in terms of durability seems to be obvious. Main causes of flexible ureteroscope repair were represented by loss of deflection, perforation of inner lining by laser fiber, and breakdown of optical fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The number of urologists using a single ureteroscope, experience of the endoscopist, location of the pathology, use of accessory instruments, duration of procedure and scope handling in between cases may all play a role in flexible ureteroscope trauma. [33] Historically, the number of procedures performed before a flexible ureteroscope requires repair averaged 6–15. However, by incorporating new ureteroscopic accessories, such as nitinol devices, a ureteral access sheath and the 200 µ holmium laser fiber into common practice, one can reduce the strain on fragile 7.5-F endoscopes, thereby maximizing their longevity.…”
Section: Durability Of Scopesmentioning
confidence: 99%
“…Channel perforation was directly attributable to damage by a laser fiber in all instances. [33] Hence care must always be exercised when advancing any laser fiber through the working channel, because these fibers are capable of penetrating the wall of instruments if passed while the scope is deflected. Therefore, straightening the tip of the ureteroscope will allow for easy passage of the laser fiber before manipulating the ureteroscope into the LC.…”
Section: Durability Of Scopesmentioning
confidence: 99%
“…1,2 There is a wide range in the rate of damage of fURSs and repair costs. [3][4][5] There are insufficient data about the proper distance between the laser fiber's tip and the scope to avoid instrumental damage caused by cavitation bubbles. We performed an observational study to evaluate the best position for the laser fiber to avoid fURS tip damage.…”
Section: Introductionmentioning
confidence: 99%